Pengaruh Kepemimpinan, Budaya Organisasi, Motivasi Kerja Dan Kepuasan Kerja Terhadap Kinerja Pegawai Pada Kantor SAR Sorong - Brury, Monce (Universitas Sam Ratulangi, 2016)
Satisfaction and dissatisfaction that felt in performing the duties of employees is constantly always exist within an organization. This research aims to determine the effect of leadership,organization culture, motivation and job satisfaction to employee performance. Location on research conducted at the Office of the SAR Sorong with a sample of 78 employees. The dataanalysis in this research is done by using multiple regression analysis. The results showed that the leadership have a significant effect on employee performance for 0.000, organization culture significant effect on the performance of employees amounted to 0.012, motivationsignificant effect on the performance of employees by 0010, job satisfaction significant effect on the performance of employees amounted to 0.007, and leadership, organizational culture,motivation employment and job satisfaction have a significant effect jointly to employee performance for 0000.Keywords: leadership, organization culture, motivation employment, job satisfaction andemployee performance